2009
DOI: 10.1021/bi901480g
|View full text |Cite
|
Sign up to set email alerts
|

H135A Controls the Redox Activity of the Sco Copper Center. Kinetic and Spectroscopic Studies of the His135Ala Variant of Bacillus subtilis Sco

Abstract: Sco-like proteins contain copper bound by two cysteines and a histidine residue. Although their function is still incompletely understood, there is a clear involvement with the assembly of cytochrome oxidases which contain the Cu A center in subunit 2, possibly mediating the transfer of copper into the Cu A binuclear site. We are investigating the reaction chemistry of BSco, the homologue from B. subtilis. Our studies have revealed that BSco behaves more like a redox protein than a metallochaperone. The essent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(57 citation statements)
references
References 44 publications
4
53
0
Order By: Relevance
“…Both proteins share a thioredoxin fold and bind copper ions through a functional CX 3 C motif complemented by a histidine residue located in a β-hairpin absent in thioredoxins (24)(25)(26)(27). This CX 3 CX n H motif allows Sco proteins either to bind Cu(I) with high affinity or to act as thioloxidoreductases (27)(28)(29). Both Sco1 and Sco2 are essential for Cu A biogenesis in humans, but their specific roles are unknown, and a detailed mechanism for Cu A assembly in mammalian oxidases is still lacking.…”
Section: Sco Proteinsmentioning
confidence: 99%
“…Both proteins share a thioredoxin fold and bind copper ions through a functional CX 3 C motif complemented by a histidine residue located in a β-hairpin absent in thioredoxins (24)(25)(26)(27). This CX 3 CX n H motif allows Sco proteins either to bind Cu(I) with high affinity or to act as thioloxidoreductases (27)(28)(29). Both Sco1 and Sco2 are essential for Cu A biogenesis in humans, but their specific roles are unknown, and a detailed mechanism for Cu A assembly in mammalian oxidases is still lacking.…”
Section: Sco Proteinsmentioning
confidence: 99%
“…Another protein conserved among most of the living organisms and well known as essential for the CcO system is Sco1. The notion of a multifunctional protein is suggested for Sco-type proteins, which may exhibit two or more distinct roles (37,38). Sco1 has first been described as a metallochaperone involved in copper transfer to the CcO system.…”
Section: Figure 7 Acop Interacts With the Cytochrome C Cyc1 (Spr Exmentioning
confidence: 99%
“…Sco1 has first been described as a metallochaperone involved in copper transfer to the CcO system. More recently, it has been suggested that Sco1 might also behave like a redox protein (37); and a tight association with the fully assembled CcO complex suggests another unknown role than the transient post-translational CcO maturation protein (38). Even if there is no sequence similarity between Sco1 and AcoP, similar multifunctional properties are now demonstrated for both proteins.…”
Section: Figure 7 Acop Interacts With the Cytochrome C Cyc1 (Spr Exmentioning
confidence: 99%
“…4550 Quite interestingly, binding of both Cu(II) and Cu(I) to Sco1 has been proposed to be important for normal functioning of this protein. 5153 Alternatively, it has been proposed that Sco1 acts as disulfide reductase to keep the active site Cys of Cu A in the reduced state or to maintain a proper redox buffering of metal ions. The latter inference stems from the fact that Sco1 possesses the thioredoxin fold.…”
Section: Introductionmentioning
confidence: 99%